2017
DOI: 10.4149/bll_2016_118
|View full text |Cite
|
Sign up to set email alerts
|

In vitro expression of HPV16 E7 linked to HMGB1 immunoadjuvant in mammalian cells

Abstract: BACKGROUND: E7 is the major transforming protein of human papillomavirus (HPV) that plays important role in maintaining the proliferative state in HPV-infected cells. Furthermore, high mobility group 1 protein (HMGB1) is a highly conserved component of chromatin that can be secreted by macrophages and activated monocytes and thus functions as an infl ammation mediator. METHODS: In the current study, cloning of HMGB1 gene and also HPV16E7-HMGB1 was performed in pEG-FP-N1 eukaryotic expression vector in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In this study, DNA sequencing analysis suggests that we successfully obtained recombinant plasmids carrying wild-type SLC26A4, mutant 1 (c.85G>A), mutant 2 (c.2006A>T), and mutant 3 (c.853G>A). pEGFP-N1, a eukaryotic expression vector encoding GFP, is commonly used to detect the expression of inserted genes via examination of GFP by fluorescence microscopy and Western blot [ 16 ]. After transfection of HEK-293T cells with these plasmids, we found that HEK-293T cells transfected not only with empty vector but also with wild-type SLC26A4 and mutants exhibited obvious GFP fluorescence and upregulated GFP expression compared to control cells, indicating successful transfection of these plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, DNA sequencing analysis suggests that we successfully obtained recombinant plasmids carrying wild-type SLC26A4, mutant 1 (c.85G>A), mutant 2 (c.2006A>T), and mutant 3 (c.853G>A). pEGFP-N1, a eukaryotic expression vector encoding GFP, is commonly used to detect the expression of inserted genes via examination of GFP by fluorescence microscopy and Western blot [ 16 ]. After transfection of HEK-293T cells with these plasmids, we found that HEK-293T cells transfected not only with empty vector but also with wild-type SLC26A4 and mutants exhibited obvious GFP fluorescence and upregulated GFP expression compared to control cells, indicating successful transfection of these plasmids.…”
Section: Discussionmentioning
confidence: 99%